Relative Stability of Membrane Proteins in Escherichia coli - Schroer, Dean W. (1981)
The relative stability of membrane proteins in Escherichia coli was investigated to determine whether these proteins are degraded at heterogeneous rates and, if so, whether the degradative rates are correlated with the sizes or charges of the proteins. Cells growing in a glucose-limited chemostat with a generation time of 15 h were labeled with [(14)C]leucine. After allowing 24 h for turnover of (14)C-labeled proteins, the cells were labeled for 15 min with [(3)H]leucine. By this protocol, the rapidly degraded proteins have a high ratio of (3)H to (14)C, whereas the stable proteins have a lower ratio. The total cell envelope fraction was collected by differential centrifugation, and the proteins were separated by two-dimensional polyacrylamide gel electrophoresis. The relative ratio for each protein was determined by dividing its (3)H/(14)C ratio by the (3)H/(14)C ratio of the total membrane fraction. Although most of the 125 membrane proteins had relative ratios close to the average for the total membrane fraction, 19 varied significantly from this value. These differences were also observed when the order of addition of [(14)C]leucine and [(3)H]leucine was reversed. In control cultures labeled simultaneously with both isotopes, the relative ratios of these 19 proteins were similar to that of the total membrane fraction. Thirteen of these proteins had low relative ratios, which suggested that they were more stable than the average protein. An experiment in which the normal labeling procedure was followed by a 60-min chase period in the presence of excess unlabeled leucine suggested that the low relative ratios of 3 of these 13 proteins may be due to a slow post-translational modification step. Six membrane proteins had high relative ratios, which indicated that they were degraded rapidly. In contrast to the relationships found for soluble proteins in mammalian cells, there were no strong correlations between the degradative rates and either the isoelectric points or the molecular weights of membrane proteins in E. coli.